DETERMINATION OF pH EFFECT AND CAPACITY OF HEAVY METALS ADSORPTION BY WATER HYACINTH (Eichhornia crassipes) BIOMASS - Anis Shofiyani; Gusrizal Gusrizal (Indonesian Journal of Chemistry, 2006)
Effect of pH and determination of adsorption capacity of Cu(II), Ni(II) and Pb(II) heavy metal ions on adsorbent prepared from Eichhornia crassipes (eceng gondok) biomass has been investigated. The influence of media acidity on the adsorption characteristics was carried out by determining ions adsorbed at various pH in the range of 2-10, while an adsorption isotherm model of Langmuir was used to estimate the capacity of adsorption. Results showed that Cu(II) was optimally adsorbed at the range pH of 5-6, Ni(II) at 2-4, while Pb(II) reached an optimum adsorption at pH 2-3. The adsorption data of Cu(II), Ni(II) and Pb(II) for the adsorbent folowed quite well Langmuir isotherm model, confirmed that such chemisorptions involved on that process. The ions adsorption capacities (am) were 27.47, 16.69, and 15.04 mg/g for Pb(II), Cu(II), and Ni(II), respectively.